MAKING MULTIPLE OF MULTI-POLY CULULOSE COMPOSITE POLYCULOSE FOR SEPARATION OF TEXTILE COLOR DYES - Heru Pratomo (Jurnal Penelitian Saintek, 2005)
The purpose   of  this  work  is,  to  determine  the  role  of  supportcomposite polysuljone  -  cellulose  acetate  membrane  in separating textile dyes. The subject is the textile dyes, and the object is dispersing textile dyes. The solution  of the textile dyes (red, yellow  and blue) made as wastewater from  textile industry. It can be concluded that the support composite polysuljone  - cellulose acetate membrane showed good permeability and high permsefectivity in separating textile dyes.